Peran Orang Tua Dalam Meningkatkan Karakter Remaja Melalui Quality Time - Marisa Aulia Gea; Difly Praise Malelak (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The importance of good character building has become a major concern, considering that it is very influential in the formation of moral foundations and individual behavior. Adolescent character is something that is very crucial to be considered by parents through quality time. This research focuses on the role of parents in improving children's character through quality time. This research uses a descriptive qualitative approach using the literature study method, this research emphasizes an in-depth understanding of this phenomenon through detailed descriptions. The results show that parents have a role as the main role model in improving adolescent character. Parents have a huge responsibility in educating their children. In conclusion, the emphasis on qualoity time in improving adolescent character is an important foundation in improving character with parents having a central role in this process as the main moral pillar and guidance for adolescents.